Особливості інституту відповідальності юридичних осіб за вчинення корупційного правопорушення в Україні - Чемерис, І.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье анализируется институт ответственности юридических лиц за совершение коррупционных правонарушений в Украине. Рассматривается опыт отдельных стран относительно ответственности юридических лиц за совершение коррупционных правонарушений. Предлагаются меры для усовершенствования деятельности в сфере противодействия коррупции юридических лиц. The article presents an analysis of the institute of responsibility for organizations in the sphere of corruption commiments in Ukraine. There are considered an experience of some countries for responsibility of organizations in the sphere of corruption commiments, proposed the perfection measures for activities in the sphere of corruption counteraction for organizations.